Nurse's role in care of children with type 1 Diabetes mellitus (Research, Society and Development, 2024)
Type 1 Diabetes Mellitus (DM1), defined as a chronic condition that has been affecting thousands of people, is considered a public health issue. The incidence of this disease is common in children. DM1, which represents 5 to 10% of cases worldwide, reaching 34 million people, can occur at any age. Objective: To describe the role of nurses in the control of DM1 in children, according to the literature. Methodology: Narrative Review of Literature of qualitative and exploratory nature. A literature review was conducted to explore and understand the role of nurses in the care of children with type 1 diabetes mellitus. Results: 20 articles were identified, selected and generated the construction of the results. A search was conducted in the Latin American and Caribbean Health Sciences Literature (Lilacs), Pubmed/Medline, and Scientific Electronic Library Online (Scielo) databases. The search has spanned the last 5 years. Final Considerations: the nurse's performance in relation to health care makes it possible to act with strategies in relation to emotional support for the child and the family, making the child with DM1 lighter, living a routine, but with quality of life and providing well-being.